The Relationship Between Sleep Hygiene and Sleep Quality in Non-Shift Worker - Khonsa Sefa Wicaksono; Pricilla Yani Gunawan (Medicinus, 2026)
Background: Impaired sleep quality is the most frequently encountered problem. The prevalence of sleep quality disorders in Indonesia reaches 10% of the population. Sleep quality can occur due to many things, one of which is poor sleep hygiene behavior. The level of sleep hygiene behavior and poor sleep quality will reduce productivity in permanent employees.   Methods: This research used a cross-sectional study with a sample size of 109 employees using a purposive sampling technique. This research will be carried out by filling out a questionnaire.   Result: Of the 109 subjects, 24 people (22.0%) had moderate-severe sleep hygiene, while 85 people (78.0%) had good sleep hygiene. Based on PSQI, 102 people (93.6%) experienced bad sleep disorders and 7 people (6.4%) did not experience sleep disorders. There was no statistically significant relationship (P = 0.648).   Conclusions: There is no statistically significant relationship between sleep hygiene and sleep quality.